Bridging landscape and perceived restorativeness: an empirical study of greenways along the Grand Canal, Hangzhou - Wang, Yue; Yang, Mengjie; Lu, Yijun; He, Qiaoyi; Zhang, Youli; Wang, Qiaoqiao; Wang, Bohao; Ruan, Xinmiao; Chen, Youjin; Zhang, Xinyue; Yang, Guofu (Frontiers in Psychology, 2026)
ContextAlthough numerous studies have shown that urban riverside greenways benefit mental health, the mechanisms through which landscape design, particularly ecological design, and influences psychological restoration remain underexplored.ObjectivesThis study addresses this gap by investigating the potential nonlinear effects of design elements (including plant design, ecological design, path design, and facility design across four dimensions and 17 indicators) on psychological restoration. Specifically, exploring the impact of various elements on psychological restoration and assesses the differences in the contributions of each design dimension to psychological restoration.MethodsThis study focuses on the Hangzhou section of the Beijing-Hangzhou Grand Canal, tracking 1,052 questionnaires to collect data on design element evaluations and psychological restoration perceptions.ResultsThe results show that: (1) in landscape design, the combination of plant design, ecological design, and facility design significantly outperforms any single element or two-element combinations in terms of restorative effects, demonstrating a synergistic effect; (2) in terms of specific mechanisms, plant color, permeable pavements, and facility quality exhibit a U-shaped relationship with psychological restoration, while ecological revetments show an inverted U-shaped relationship; (3) vegetation coverage, plant color, and resting facilities are key factors in promoting psychological restoration.ConclusionThis study reveals the synergistic and nonlinear effects of landscape design in urban riverside greenways on psychological restoration, providing valuable design dosage references for urban planners and designers. It offers important insights for the future design of urban riverside greenways that harmonize landscape and human health.